2017
DOI: 10.33590/emjgastroenterol/10313415
|View full text |Cite
|
Sign up to set email alerts
|

Editor’s Pick: Recent Advances in the Diagnosis and Management of Abdominal Tuberculosis

Abstract: Abdominal tuberculosis and its protean manifestations still create a diagnostic challenge for clinicians and remain an important concern in the developing world. Crohn’s disease, which is being increasingly recognised in countries where intestinal tuberculosis is prevalent, needs to be differentiated as the two diseases resemble each other in their clinical presentation, and in their radiological, endoscopic, and histological findings. New diagnostic modalities and scoring systems have facilitated the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 54 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Logan's modification of Paustian's criteria is often followed since it allows the diagnosis of abdominal TB based on a response to a trial of antitubercular treatment (ATT). 3 This approach has its drawbacks as well, since many other diseases may be wrongly treated with ATT, and to add to the confusion, few of the nontubercular diseases may show some response as well. Subsequently in a study, it was shown that clinical response coupled with mucosal response is diagnostic of intestinal TB in this setting and especially to differentiate from Crohn's disease.…”
Section: Introductionmentioning
confidence: 99%
“…Logan's modification of Paustian's criteria is often followed since it allows the diagnosis of abdominal TB based on a response to a trial of antitubercular treatment (ATT). 3 This approach has its drawbacks as well, since many other diseases may be wrongly treated with ATT, and to add to the confusion, few of the nontubercular diseases may show some response as well. Subsequently in a study, it was shown that clinical response coupled with mucosal response is diagnostic of intestinal TB in this setting and especially to differentiate from Crohn's disease.…”
Section: Introductionmentioning
confidence: 99%
“…3 Peritoneal TB and intestinal TB are the most prevalent forms, which accounts for ~31-58% and ~40%, respectively, of abdominal TB. 4,5 Abdominal TB occurs either as a primary or secondary infection owing to reactivation of latent TB lesions elsewhere, that is, lung, kidney, and fallopian tube. Diagnosis of abdominal TB is an off-putting challenge owing to paucibacillary nature of specimens and non-specific clinical presentations that imitate other abdominal diseases, for example, Crohn's disease and malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Abdominal TB involves any part of the gastrointestinal system, lymph nodes, peritoneum or other visceral organs, such as the pancreas, liver or spleen, among others 3 . Peritoneal TB and intestinal TB are the most prevalent forms, which accounts for ~31–58% and ~40%, respectively, of abdominal TB 4,5 . Abdominal TB occurs either as a primary or secondary infection owing to reactivation of latent TB lesions elsewhere, that is, lung, kidney, and fallopian tube.…”
Section: Introductionmentioning
confidence: 99%
“…Abdominal TB constitutes 3%-6.7% of cases with extrapulmonary TB, and peritoneal involvement is common. [1,2] An increased risk of TB has been demonstrated with the use of TNF-α antagonist. Anti-TNF drugs can cause the breakdown of granulomas in latent infection.…”
mentioning
confidence: 99%